Hubungan Penyesuaian Diri Dengan Stres Akademik Pada Mahasiswa Yang Mengambil Mata Kuliah Proposal Skripsi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The objectives of this study are: (1) to see how high the level of self-adjustment is experienced by students who take thesis proposal courses, (2) to see how high the level of academic stress experienced by students who take thesis proposal courses is, (3) to find out whether there is a relationship between self-adjustment and academic stress in students, (4) to identify items on the self-adjustment scale and academic stress scales that are not optimal (low), So that it can be proposed as a topic of classroom guidance with students. This research method uses correlational quantitative research with a total of 100 student respondents. The analysis techniques used in this study used categorization, normality test, linearity test and correlational hypothesis test. The results of this study stated that: 1) the level of self-adjustment of students who prepared thesis proposals was included in the low category with a percentage of 36% of students who were in the low category. 2) the level of academic stress in students who took thesis proposal courses was in the high category with a percentage of 43%, 3) there was a positive relationship between self-adjustment and academic stress which was of high significance with Pearson's value of -0.513 and p <.001, 4) there were 18 items on the self-adjustment scale that were included in the low category, 1 item in the very low category, and 2 items on the academic stress scale that are included in the low category.